Comparative analysis of message brokers - Kaczor, Mateusz; Powroźnik, Paweł (Journal of Computer Sciences Institute, 2022)
The article presents a comparative analysis of the two most popular message brokers: Apache Kafka and RabbitMQ. The purpose of this paper was to perform a comparative analysis of selected technologies and to determine their time efficiency. For the needs of the research four applications were prepared (two for each tested technology) that were sending and receiving messages. The research was supplemented with tests with the use of auxiliary tools and theoretical comparison. The comparative analysis of gathered data allowed us to determine the most effective technology, which happened to be Apache Kafka.